2012
DOI: 10.2174/156800912800190929
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiogenesis Inhibitors in Colorectal Cancer: Sensitive and Insensitive Tumors

Abstract: Angiogenesis is a key factor in the carcinogenesis process. In oncological practice, angiogenesis inhibition, mainly through the blockade of the VEGF family and its receptors, has been robustly demonstrated to produce clinical benefits and, in specific disease subsets such as colorectal cancer, to extend the overall survival of treated patients. VEGF is a multifunctional growth factor that mediates its functions through cognate receptors on endothelial cells and it has been discovered for its capability to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 120 publications
(135 reference statements)
2
17
0
Order By: Relevance
“…Angiogenesis has been found to play an important role in the growth and migratory potential of colon cancer (Bagnasco et al 2012). In the present study, we further examined whether BDNF regulates expression of the angiogenic factor VEGF in HCT-116 cells.…”
Section: Bdnf-directed Colon Cancer Cell Migration Involves Vegf Exprmentioning
confidence: 94%
“…Angiogenesis has been found to play an important role in the growth and migratory potential of colon cancer (Bagnasco et al 2012). In the present study, we further examined whether BDNF regulates expression of the angiogenic factor VEGF in HCT-116 cells.…”
Section: Bdnf-directed Colon Cancer Cell Migration Involves Vegf Exprmentioning
confidence: 94%
“…Currently, the approved agents for treatment of CRC include monoclonal antibodies or small molecule tyrosine kinase inhibitors against the epidermal growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) pathways, as well as the standard chemotherapeutic agents 5-FU, irinotecan, and oxaliplatin (Ortega et al, 2010; Bagnasco et al, 2012; Strumberg et al, 2012). Current research in this disease is primarily focused on various iterations of these therapies, while novel agent development is stalled.…”
Section: Introductionmentioning
confidence: 99%
“…22,40 In clinical practice, angiogenesis inhibition by way of vascular endothelial growth factor (VEGF) blockade is demonstrated to produce a great number of benefits. 41,42 Nevertheless, resistance to VEGF inhibitors is emerging as a significant problem of clinical oncology. 18 Fortunately, some studies have found that blockade of DLL4 results in non-productive angiogenesis with an inhibitory effect on tumour growth, including tumour resisted to VEGF inhibitors.…”
Section: Discussionmentioning
confidence: 99%